Neurosurgery Principles and Practice - Moore, Anne J.; Newell, David W.; SpringerLink (Online service) (London : Springer London, 2005)
2 3 4 5 6 7 8 9 1011 1 2 3 4111 This book provides coverage of a broad range of topics in the ?eld of neurosurgery, 5 for residents and registrars in training and for recent graduates of training programs. 6 As neurosurgical training incorporates expertise from centers worldwide, there is a 7 need to have input from specialists in neurosurgery from various countries. This text 8 is a compilation by expert authors in the USA and the UK to provide information on 9 the basic knowledge and clinical management required for optimal care of neuro- 2011 surgical patients. 1 The text is an up-to-date synopsis of the ?eld of neurosurgery from American and 2 British perspectives, which covers the most common clinical conditions encountered 3 by neurosurgeons. The chapters are organized under broad topics, including inves- 4 tigative studies, perioperative care, the role of newer techniques and the management 5 of tumors, vascular and traumatic lesions. Additional topics are then covered, includ- 6 ing pediatrics, spine and peripheral nerve lesions, as well as functional neurosurgery 7 and infections. We anticipate that trainees will ?nd this information useful for certi?- 8 cation examinations and recent graduates of neurosurgical training programs can 9 utilize this text as an update of the most important neurosurgical topics.
Investigations -- Neurophysiology -- Neuroradiology and Ultrasound -- Neuropathology -- Perioperative Care -- Neuroanesthesia -- Neurosurgical Intensive Care -- Techniques -- Neuroendoscopy -- Principles and Practice of Image-guided Neurosurgery -- Stereotactic Radiosurgery -- Tumors -- Low-grade Gliomas in Adults -- Neurosurgical Management of High-grade Gliomas -- Sellar and Parasellar Tumors -- Meningiomas -- Intraventricular and Pineal Region Tumors -- Cerebello-pontine Angle Tumors -- Skull Base Tumors -- Tumors: Cerebral Metastases and Lymphoma -- Vascular -- Cerebral Blood Flow: Physiology and Measurement Techniques -- Aneurysmal Subarachnoid Hemorrhage -- Interventional Neuroradiology -- Arteriovenous Malformations -- Trauma -- Management of Severe Head Injury -- Spine Injuries -- Rehabilitation of Neurologically Injured Patients -- Hydrocephalus -- Hydrocephalus and Shunts -- Pediatrics -- Craniosynostosis -- Syndromic Craniosynostosis -- Spinal Dysraphism -- Pediatric Neuro-oncology -- Spine -- Management of Spinal Tumors -- Management of Extradural Spinal Tumors -- Degenerative Disease of the Cervical Spine -- Peripheral and Cranial Nerves -- Peripheral and Cranial Nerve Injury -- Functional Neurosurgery -- Pain -- Epilepsy Surgery -- Functional Neurosurgery for Movement Disorders -- Infection -- Infections in the Central Nervous System -- Infections in Neurological Surgery -- Ischemic Stroke and Carotid Endarterectomy.
Keywords: Medicine; Neurology; Neurosurgery; Surgery; Medicine & Public Health; Neurology; Neurosurgery; Surgery; Electronic books